Imagens de transformação e resistência na apropriação do espaço urbano de Belo Horizonte - Elisangela Batista da Silva (2020)
This research proposes a study on how urban art has changed the urban landscape of Belo Horizonte and, consequently, its image. Since the 1960s, several panels have been painted on murals around the city, but it is from the 1990s that giant murals of Hugues Desmaziéres and his disciple Douglas Melo appear, which serve as inspiration for the emergence of the Urban Circuit of Art - CURA, which through festivals has reinterpreted the city with themes that arouse interest and debate. Urban art, through graffiti, muralism and graffiti, is present in walls, gables, viaducts, urban equipment. To investigate this scenario, we started from the premise that urban art could be considered as constituent bases of the social practice of urban space in the city. And if the processes of occupation, appropriation and intervention in the city can be understood as promoting political and social issues. Because it is an art that says a lot about the city, it transgresses, but it is also legalized. To understand this scene, we sought theoretical support in the theory of space and the dialectic triad of Henri Lefebvre and in the mediological studies of Régis Debray. The theory of space, together with the right to the city, provides an understanding of the social practice of space. And the midiological eras clarify the place of the image as a social sign, which associated with Lefebvrian theories give theoretical support to this research. Research was carried out with a survey of mixed quantitative and qualitative data, with residents and passers-by of Belo Horizonte, to understand what their perception is in relation to this scenario. And a qualitative research with an interview with urban artists and producers of the urban scene, who are active agents of this panorama.